High-Resolution Monitoring of Temperature, Conductivity, and pH natural variability from September to November 2021 in Gorgona Island, Colombian Pacific - Murcia Zambrano, Paula Andrea (PANGAEA, 2024)
Continuous measurements of pH total scale, conductivity (mS cm⁻¹), and temperature (°C) were conducted from September 8 to November 19, 2021, at El Muelle reef, Gorgona Island, Colombian Pacific, Panama Bight, at a depth of two meters using a buoy anchoring system as part of the "Ocean acidification vulnerability in Colombia: first monitoring program in the Tropic Pacific" project. The iSAMI-pH equipment, programmed with SAMI Client v2.5 software, was used to record pH total scale and temperature. Likewise, CTD Diver equipment, programmed with Diver Field software, was used to take data for pressure and conductivity. Data were taken every 30 minutes from September 8 to 13, 2021; every 3 hours from September 14 to November 7, 2021, and every 1.5 hour from November 8 to 19, 2021.
Keywords: Conductivity; continuous measurements; CTD Diver; iSAMI-pH; Panama Bight; pH total scale; Temperature